François-Louis Comte de Castelnau (1802–1880) and the mysterious disappearance of his original insect collection - Evenhuis, Neal L. (Zootaxa, 2012)
A brief biography of François Louis Comte de Castelnau is presented, correcting his birthdate and surname, and the ultimate fate of his original personal collection of insects and other natural history material is discussed.